Agent-Based Modeling for Urban Development Planning based on Human Needs. Conceptual Basis and Model Formulation. (February 2021) - González-Méndez, Mauricio; Olaya, Camilo; Fasolino, Isidoro; Grimaldi, Michele; Obregón, Nelson
Highlights: Cities are complex socioecological systems that are product of human interactions. Conventional urban policy models have focused on economic activities and markets. We develop an engineering approach to urban planning operationalized in an agent based model (ABM). The core of the model is the relationship between physical environment and human needs. The simulation platform design can be extended to involve participatory modelling. Abstract: A city comprises an ecological environment, a living and architectural space, the product of a history of human interactions that determines its morphology and destiny. Cities are complex systems that encompass elements of diverse types, such as natural objects, technical artifacts, human actors and social entities, including the rules or laws governing their behavior. Despite cities complexity, conventional urban policy models have focused on expanding and building places geared toward satisfying economic activities and markets. In this paper we propose an agent based model (ABM) for urban development planning based on the relationship between city inhabitants and the satisfaction of their basic needs with their physical environment. Our design recognizes human complexity within the urban contexts and establishes a new method for planning city development with the help of a tool geared toward simulating participation. This simulation platform makes it possible to consider the effects of human behavior as a determinant of the success or failure of urban interventions from the point of view of planning. The central elements of the simulation model are the relationship of each individual to the physical environment of the city and the satisfaction of their basic needs. This simulation platform can be used as a starting point on a collective and prospective vision of the city, grounded in the approach and experience of participatory modeling with multiple stakeholders.